Importancia de los Agentes Alelopáticos en el Manejo Integrado de Cultivos - Nieto Ayala, Dámaris Shalom (2021)
The growing world population, together with a number of factors that threaten the stability of ecosystems, such as climate change and pesticide abuse, are producing less productive areas, and therefore less land dedicated to agricultural use. These facts make research on the most productive varieties that generate profitable, ecological and non-polluting agriculture a priority today. In nature, plants were subjected, throughout their history, to different biotic and abiotic components that have exerted a selection pressure, which will appear to evolve by developing different metabolic pathways through which they synthesize a gigantic variety of metabolites. secondary. Several of these secondary metabolites (known as allelopathic or allelochemical agents) have the potential to generate inhibition or stimulation in recipient organisms. These qualities can be beneficial in the Integrated Crop Management approach using allelopathy as a minimizer of weeds, controlling pests and reducing the populations of pathogens in field areas. The use of allelopathic plants turns out to be one of the agroecological alternatives, this is defined as the harmful or stimulatory effect that microorganisms and plants have the possibility of exerting on others.